ORGANIZATIONAL BASES OF FARM ACTIVITIES - A.M.Axmedov; I.B.Sapayev; R.U.Abduhamidova; N.D.Rustamov; M.Sh.Shukurova; Z.A.Abduvaliyev; L.Q.Turobov; Sh.M.Usanov (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
One of the important issues in the period after the world financial and economic crisis is to optimize the activities of farms and reduce production costs and optimize costs based on the analysis of their activities. In this context, “Agriculture and Water Management is very serious about the study and implementation of modern agro-technologies, the further improvement of selection works and the increase of the productivity of agricultural production. it is necessary to develop a set of specific measures." As a result of measures implemented to support and develop farmers and peasant farms, which are the main producers of agricultural goods, their role in the economy is increasing year by year. In the following years, work was carried out on the optimization of farm land areas.